Temporal logic for social networks. (15th March 2022) - Machado, Vitor; Benevides, Mario
Abstract: This paper introduces a logic with a class of social network models that is based on standard Linear Temporal Logic, which allows for leveraging the power of existing model checkers for the analysis of social networks. We provide a short literature overview, and then define our logic and its axiomatization, present some simple motivational examples of both models and formulas and show its soundness and completeness via a translation into propositional formulas. Lastly, we discuss model checking, time complexity analysis and a Susceptible–Infectious–Recovered model variation for infectious diseases.